The Lectin Complement Pathway Is Involved in Protection Against Enteroaggregative Escherichia coli Infection - Adler Sørensen, Camilla; Rosbjerg, Anne; Hebbelstrup Jensen, Betina; Krogfelt, Karen Angeliki; Garred, Peter (Frontiers in Immunology, 2018)
Enteroaggregative Escherichia coli (EAEC) causes acute and persistent diarrhea worldwide. Still the involvement of host factors in EAEC infections is unresolved. Binding of recognition molecules from the lectin pathway of complement to EAEC strains have been observed, but the importance is not known. Our aim was to uncover the involvement of these molecules in innate complement dependent immune protection towards EAEC. Binding of mannose-binding lectin, ficolin-1,-2 and -3 to four prototypic EAEC strains, and ficolin-2 binding to 56 clinical EAEC isolates were screened by a consumption based ELISA method. Flow cytometry was used to determine deposition of C4b, C3b and the bactericidal C5b-9 membrane attack complex (MAC) on the bacteria in combination with different complement inhibitors. In addition, the direct serum bactericidal effect was assessed. Screening of the prototypic EAEC strains revealed that ficolin-2 was the major binder among the lectin pathway recognition molecules. However among the clinical EAEC isolates only a restricted number (n = 5) of the isolates bound ficolin-2. Using the ficolin-2 binding isolate C322-17 as a model, we found that incubation with normal human serum led to deposition of C4b, C3b and to MAC formation. No inhibition of complement deposition was observed when a C1q inhibitor was added, while partial inhibition was observed when ficolin-2 or factor D inhibitors were used separately. Combining the inhibitors against ficolin-2 and factor D led to virtually complete inhibition of complement deposition and protection against direct bacterial killing. These results demonstrate that ficolin-2 may play an important role in innate immune protection against EAEC when an appropriate ligand is exposed, but many EAEC strains evade lectin pathway recognition and may therefore circumvent this strategy of innate host immune protection.